Cyclin dependent kinase 4/6 inhibitor palbociclib synergizes with BCL2 inhibitor venetoclax in experimental models of mantle cell lymphoma without RB1 deletion - Maláriková, Diana; Jorda, Radek; Kupcová, Kristýna; Senavova, Jana; Dolnikova, Alexandra; Pokorna, Eva; Kazantsev, Dmitry; Nozickova, Kristina; Sovilj, Dana; Bellanger, Celine; Chiron, David; Andera, Ladislav; et al. (Experimental hematology & oncology, 2024)
BACKGROUND: Mantle cell lymphoma (MCL) is a chronically relapsing malignancy with deregulated cell cycle progression. We analyzed efficacy, mode of action, and predictive markers of susceptibility to palbociclib, an approved CDK 4/6 inhibitor, and its combination with venetoclax, a BCL2 inhibitor. METHODS: A panel of nine MCL cell lines were used for in vitro experiments. Four patient derived xenografts (PDX) obtained from patients with chemotherapy and ibrutinib-refractory MCL were used for in vivo proof-of-concept studies. Changes of the mitochondrial membrane potential, energy-metabolic pathways, AKT activity, and pro-apoptotic priming of MCL cells were evaluated by JC-1 staining, Seahorse XF analyser, genetically encoded fluorescent AKT reporter, and BH3 profiling, respectively. MCL clones with gene knockout or transgenic (over)expression of CDKN2A, MYC, CDK4, and RB1 were used to estimate impact of these aberrations on sensitivity to palbociclib, and venetoclax. RESULTS: Co-targeting MCL cells with palbociclib and venetoclax induced cytotoxic synergy in vitro and in vivo. Molecular mechanisms responsible for the observed synthetic lethality comprised palbociclib-mediated downregulation of anti-apoptotic MCL1, increased levels of proapoptotic BIM bound on both BCL2, and BCL-XL and increased pro-apoptotic priming of MCL cells mediated by BCL2-independent mechanisms, predominantly palbociclib-triggered metabolic and mitochondrial stress. Loss of RB1 resulted in palbociclib resistance, while deletion of CDKN2A or overexpression of CDK4, and MYC genes did not change sensitivity to palbociclib. CONCLUSIONS: Our data strongly support investigation of the chemotherapy-free palbociclib and venetoclax combination as an innovative treatment strategy for post-ibrutinib MCL patients without RB1 deletion.